Influência de transformação martensítica a baixa temperatura no nível de tensões residuais e textura cristalográfica de juntas soldadas de aços usados na indústria do petróleo - Tavares, Wellison da Silva (2013)
The filler metal of martensitic stainless steels has its used welding of alloy ferritic / martensitic to provide suitable mechanical strength and corrosion. This research accomplishes a study of the mechanical and metallurgical properties correlate with the crystallography texture and variants selection during the martensitic transformation in the weld metal. The filler metal used was Fe-12% Cr-5% Ni, with martensitic transformation temperature less than 200°C, welding sections of steel pipeline API 5L grade B used in oil extraction and structure offshore. The welding of the specimens was performed automatically. Samples of each layer of filling were removed for analysis during chemical composition, microhardness, microstructural characterization by optical microscopy (OM) and scanning electron microscopy (SEM), X-ray diffraction and thermo-magnetic test. It’s intend to accomplish a mapping of texture and variants selection of the formation of martensitic morphology by Electron Backscattering Diffraction (EBSD). The results have shown that residual stresses in welded joints filler metal of low-temperature martensitic transformation had higher compressive residual stress intensities compared to the common electrode, and did not influence the appearance of crystallographic texture on top of beads. The high heat input significantly influenced the increase toughness beads and contributed to the appearance of reverted austenite.